The effects of government venture capital: New evidence from China based on a two-sided matching structural model - Zhang, Jing; Fan, Yueqi; Liu, Ye (Journal of Corporate Finance, 2024)
This study develops a two-sided matching structural model to examine whether government venture capitals (GVCs) crowd out private venture capitals (PVCs) by comparing the pre-money economic valuation of observed and counterfactual investments. The structural model also allows us to study the impacts of GVCs on the post-investment performance of the funded companies. Using China's VC market data between 2000 and 2020, we find that GVC-funded companies are those neglected by PVCs, and the potential economic performance of GVC-funded companies is inferior to that of PVC-funded ones. It means that the data do not support the crowding out conjecture. Moreover, the evidence suggests that the potential innovativeness of GVC-funded companies is higher than that of PVC-funded companies, indicating that GVCs bridge the equity gap left by PVCs in innovative companies. Regarding the impacts on companies' post-investment performance, GVCs are not significantly different from PVCs in improving companies' economic performance, and they are better than PVCs in improving companies' innovative performance. We also explore the impacts of different types of GVCs, the impacts of the co-investment between GVCs and PVCs, and the impacts of GVCs on companies in different stages of development.